Hyperthermophilic endospores germinate and metabolize organic carbon in sediments heated to 80°C. (13th September 2022) - Bell, Emma; Rattray, Jayne E.; Sloan, Kathryn; Sherry, Angela; Pilloni, Giovanni; Hubert, Casey R. J.
Abstract: Cold surface sediments host a seedbank of functionally diverse thermophilic bacteria. These thermophiles are present as endospores, which are widely dispersed in aquatic environments. Here, we investigated the functional potential of endospore populations in cold surface sediments heated to 80°C. Microbial production of acetate was observed at 80°C and could be enhanced by supplying additional organic carbon substrates. Comparison of 16S rRNA gene amplicon libraries from 80°C enrichments to sediments heated to lower temperatures (50–70°C) showed that temperature selects for distinct populations of endospore‐forming bacteria. Whereas sulfate‐reducing thermophiles were enriched in 50–70°C incubations, 80°C exceeds their thermal tolerance and selects for hyperthermophilic organotrophic bacteria that are similarly detected in amplicon libraries from sediments heated to 90°C. Genome‐resolved metagenomics revealed novel carbon cycling members of Symbiobacteriales, Thermosediminibacteraceae, Thermanaeromonas and Calditerricola with the genomic potential for the degradation of carbohydrates, sugars, amino acids and nucleotides. Endospores of thermophilic bacteria are deposited on seabed sediments worldwide where they remain dormant as they are buried in the accumulating sediments. Our results suggest that endospore populations could be activated by temperature increases encountered during burial and show the potential for organotrophic metabolic activity contributing to acetate generation in deep hot sediments.